Uncommon presentation of bilateral subtrochanteric insufficiency fractures in young male associated with hypogonadism: A case report - Sulaiman, Sarmad Rasheed K.; Alturk, Yousef M.; Alarabi, Rayan M.; Alsisi, Ebtehal M.; Rajeh, Alwaleed A.; Sulaimani, Amal B. (Journal of Musculoskeletal Surgery and Research)
Hypogonadism in men is a well-recognized cause of secondary osteoporosis. It is characterized by insufficient production of androgen, testosterone, and sperms. Testosterone deficiency is the key factor for insufficiency fractures in men, resulting from normal loading on an osteoporotic bone. In this report, we are presenting a case of a 27-year-old male known to have hypogonadotropic hypogonadism, who suffered from both femoral atraumatic subtrochanteric fractures that had been existing for a considerable time. The fractures interfered with the patient’s walking and daily activity. It is worth reporting this case because most of the proximal femur insufficiency fractures mentioned in the literature correlated with prolonged alendronate therapy or were post-bariatric surgery.